Allowing for Development in the EAP Post-observation Conference: Towards a flexible observation model - Robinson, Lisa (2013)
Despite the emergence of specific English for Academic Purposes (EAP) qualifications in the UK and worldwide, EAP training remains ‘largely ad hoc and informal’ (Alexander, 2010:3). The post-observation conference (POC) is a valuable opportunity to address the development needs of EAP tutors. This dissertation explores to what extent the POC fulfils these needs by presenting a review of the relevant literature and a case study of the POC. The latter is based on the collection of six EAP tutor interviews. Analysis of the data suggests that the POCs described in this study are largely supervisory in approach, with a bias towards evaluation rather than development. Moreover, POC structure and discourse can influence this partiality and perpetuate an observer-driven event. I make recommendations for a flexible observation model which encourages a shared agenda to support tutors in taking responsibility for their own development and promotes collaboration and reflection, prerequisites for knowledge building.